3(5x+5)=-48+3

Simple and best practice solution for 3(5x+5)=-48+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(5x+5)=-48+3 equation:


Simplifying
3(5x + 5) = -48 + 3

Reorder the terms:
3(5 + 5x) = -48 + 3
(5 * 3 + 5x * 3) = -48 + 3
(15 + 15x) = -48 + 3

Combine like terms: -48 + 3 = -45
15 + 15x = -45

Solving
15 + 15x = -45

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-15' to each side of the equation.
15 + -15 + 15x = -45 + -15

Combine like terms: 15 + -15 = 0
0 + 15x = -45 + -15
15x = -45 + -15

Combine like terms: -45 + -15 = -60
15x = -60

Divide each side by '15'.
x = -4

Simplifying
x = -4

See similar equations:

| 3y+18=6 | | -3(7w+8)= | | (3y-(3x^2))/((3y^2)-3x)=0 | | 9x-20+7x+18=90 | | 8(2y-1)-3(3+2y)= | | 24+5n-8+3n=56 | | 7x-18=5x-10 | | 4/5x=8.2 | | 5(x-4)=2(x+3) | | (3y-3x^2)/(3y^2-3x)=0 | | 7x+19=9x+21 | | 6(-2+8d)= | | 9x-20+7x+18=180 | | 2x+38=3x-12 | | 7/8x(-56) | | 5x-2x-2=-2x+13 | | 13x-43+7x-1=180 | | 2y-7=y-9 | | 5y+40=20x | | 1/2*(3)*10/21 | | 1/tan(90°-x)cscx=secx-cosx | | 5(-4h+8)= | | 5x^5/3x^3 | | t^2+15t-39=0 | | 3/4-25/8 | | 8z^3-1=0 | | x+6(-9)= | | 0.9x=1.26 | | 2(20+-.05y)+y=40 | | 16-(4/3)x=4 | | 8x+19=139 | | 6w-13w-15=-17-6w |

Equations solver categories